Benzodiazepines and the potential trophic effect of antidepressants on dentate gyrus cells in mood disorders. (27th June 2014) - Boldrini, Maura; Butt, Tanya H.; Santiago, Adrienne N.; Tamir, Hadassah; Dwork, Andrew J.; Rosoklija, Gorazd B.; Arango, Victoria; Hen, René; Mann, J. John
Abstract: Modest antidepressant response rates of mood disorders (MD) encourage benzodiazepine (BZD) co-medication with debatable benefit. Adult hippocampal neurogenesis may underlie antidepressant responses, but diazepam co-administration impairs murine neuron maturation and survival in response to fluoxetine. We counted neural progenitor cells (NPCs), mitotic cells, and mature granule neurons post-mortem in dentate gyrus (DG) from subjects with: untreated Diagnostic and Statistical Manual of Mental Disorders (DSM) IV MD ( n = 17); antidepressant-treated MD (MD*ADT, n = 10); benzodiazepine-antidepressant-treated MD (MD*ADT*BZD, n = 7); no psychopathology or treatment (controls, n = 18). MD*ADT*BZD had fewer granule neurons vs. MD*ADT in anterior DG and vs. controls in mid DG, and did not differ from untreated-MD in any DG subregion. MD*ADT had more granule neurons than untreated-MD in anterior and mid DG and comparable granule neuron number to controls in all dentate subregions. Untreated-MD had fewer granule neurons than controls in anterior and mid DG, and did not differ from any other group in posterior DG. MD*ADT*BZD had fewer NPCs vs. MD*ADT in mid DG. MD*ADT had more NPCs vs. untreated-MD and controls in anterior and mid DG. MD*ADT*BZD and MD*ADT had more mitotic cells in anterior DG vs. controls and untreated-MD. There were no between-group differences in mid DG in mitotic cells or in posterior DG for any cell type. Our results in mid-dentate, and to some degree anterior dentate, gyrus are consistent with murine findings that benzodiazepines counteract antidepressant-induced increases in neurogenesis by interfering with progenitor proliferation. We also confirmed, in this expanded sample, our previous finding of granule neuron deficit in untreated MD.